The Correlation Between Indonesian Senior High School Students' Reading Comprehension and Text Readability - Indrawan, Fani; Ma’rifatulloh, Sayid; Hardinanto, Eko (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2024)
This research aims to explore the correlation of text readability and students’ reading comprehension. Researches on the readability of texts mostly aim to assess the readability level of a text and relate it to the grade level of the reader. However, this research starts from a curiosity that text readability can be connected to one of the students' language abilities that is closely related to text, reading comprehension. The method used in this study is a quantitative research design with a correlational approach. The readability formula used to measure the texts in this research is The Flesch-Kincaid Grade Level (FKGL). The participants of this study were 306 students in grades X, XI, and XII of Indonesian senior high school. The findings shows that there is a significant relationship between those two variables. This finding could help strengthen the position of text readability in academic setting especially in predicting students reading comprehension. Based on the result, the primary contribution of this research is in the exploration of the statistical relationship between text readability and reading comprehension.